PENDIDIKAN DAN PELATIHAN PENGENDALIAN TERPADU HAMA PENGGEREK BATANG PADI DI KELURAHAN PENATIH, KECAMATAN DENPASAR TIMUR, KOTA DENPASAR - Wijaya, : I Nyoman (Buletin Udayana Mengabdi, 2012)
ABSTRACT Education and training on integrated pest management (IPM) of Rice Stem Borrer has been held at Penatih village, Denpasar regency on 15 st September 2007. The activities aimed to improve knowledge farmer of Rice Stem Borrer and factors influence the intensity, and integrated pest management of Rice Stem Borrer. The topics covered were symptom, bioecology, insect distribution and integrated management of Rice Stem Borrer. The training was attended by 25 participants from local farmer groups of Penatih village. The method used in activities were lectures, demontration and practical in the rice field. All participants participited anthusiastically and hope the have the next intensive traning of the rice culture.